Trabalho, comércio e dignidade: desafios e perspectivas para a atuação conjunta da OIT e da OMC - Meireles, Gustavo Fernandes (2014)
The trade-labour linkage reaches new levels in the context of globalization and production restructuring. Production chains are getting even more internationalized and fundamental rights on labour require legal mechanisms in order to harmonise domestic labour laws amongst different countries. By adopting the earliest labour standards, countries demanded that others shall do the same. They argued on unfair trade and social dumping. In the context of globalized economy, protection of labour standards relates closely to global trade. Considering that labour is a fundamental human characteristic and is associated to dignity, this research analyses challenges and perspectives for an effective collaboration between the International Labour Organization (ILO) and the World Trade Organization (WTO) in the promotion of fundamental labour standards. ILO has early defined the principle from which labour should not be regarded merely as a commodity or article of commerce. This principle influenced labour law evolution in many countries. Beyond production of labour standards, ILO plays a role controlling the implementation of its rules. The organisation is oriented by a human rights rationality. On the other hand, the WTO is the heir of General Agreement Tariffs and Trade tradition and regulates the multilateral trade system, oriented by an economic rationality and counting on an effective dispute settlement body. Although there are many converging points leading to the trade-labour linkage, dialogue between the organisations and its legal subsystems has been barely undertaken. Labour issues had been excluded from the WTO since its early years, by the Singapore Ministerial Conference, in 1996. The study of organisations’ structures and legal subsystems reveals many converging points and opening for an effective dialogue between these subsystems. The conclusions point out perspectives for the harmonisation of ILO and WTO’s legal subsystems, overcoming some symptoms of international law fragmentation in this field and joining efforts for the promotion of decent work and fair trade.